Transreform radical humanism : a mathematics and teaching philosophy - Russell, Gale (Advances in innovation education, 2017)
Of the Traditional Western WorldviewAN INDIGENOUS WORLDVIEW; Relationship, Context, and the Whole; Relationship and Place; Relationship, Ways of Knowing, and Diversity; Connectedness: Mind and Body, Objective and Subjective; Relationship, Flux, Cycles, and a Holistic View; Relationship and Process; Relationship and Time; Relationship and Dichotomy; Relationship, Reciprocity, and the Greater Good; Relationship and Orality; Summary of an Indigenous Worldview; THE TWO WORLDVIEWS: IMPLICATIONS AND CONCERNS; CONCLUDING THOUGHTS ON THE WORLDVIEWS; METHODOLOGY AND METHODS; AUTO/ETHNOGRAPHY.